2016
DOI: 10.1093/icvts/ivw376
|View full text |Cite
|
Sign up to set email alerts
|

High preoperative monocyte count/high-density lipoprotein ratio is associated with postoperative atrial fibrillation and mortality in coronary artery bypass grafting

Abstract: We have observed that high preoperative monocyte count/ high-density lipoprotein ratio was associated with postoperative atrial fibrillation and mortality after coronary artery bypass grafting operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
3
15
1
1
Order By: Relevance
“…The rate of NSTE myocardial infarction (NSTEMI) was higher in the ISR group than in the non-ISR group (50.0% vs 16.8%, p=0.001). The rate of presence of a bifurcation lesion was higher and time between the two CAG scans was longer in the ISR group than in the non-ISR group (37.5% vs 15.3%, p=0.019; 27.5 [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] vs 23.0, [16][17][18][19][20][21][22][23][24][25][32][33][34][35] p=0.043, respectively). Angiographic and PCI results, including the rate of calcification lesion, lesion type according to the AHA classification, generation of the implanted stents, the total stent length, maximum stent diameter, and post-dilatation indication, were similar in both groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of NSTE myocardial infarction (NSTEMI) was higher in the ISR group than in the non-ISR group (50.0% vs 16.8%, p=0.001). The rate of presence of a bifurcation lesion was higher and time between the two CAG scans was longer in the ISR group than in the non-ISR group (37.5% vs 15.3%, p=0.019; 27.5 [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] vs 23.0, [16][17][18][19][20][21][22][23][24][25][32][33][34][35] p=0.043, respectively). Angiographic and PCI results, including the rate of calcification lesion, lesion type according to the AHA classification, generation of the implanted stents, the total stent length, maximum stent diameter, and post-dilatation indication, were similar in both groups.…”
Section: Resultsmentioning
confidence: 99%
“…23 Saskin et al reported that high preoperative MHR was associated with postoperative atrial fibrillation and mortality in coronary artery bypass grafting. 24 The relation of MHR with short-and long-term clinical outcome after primary PCI in ST-segment elevation myocardial infarction (STEMI) patients and atrial fibrillation recurrence after ablation procedures is also revealed. [25][26][27] All aforementioned studies showed the clinical value of MHR as a novel inflammation-based prognostic marker in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a relationship between the elevation of MHR and presence and severity of isolated coronary artery ectasia [19], asymptomatic organ damage in patients with primary hypertension [20], slow coronary flow [21], cardiac syndrome X [22], metabolic syndrome [23], infective endocarditi [24] and saphenous vein graft disease in coronary bypass [25]. It also has been reported to be related to cardiovascular outcomes in patients with chronic kidney disease [26], arterial fibrillation recurrence after cryoballoon based catheter ablation [27], mortality and arterial fibrillation recurrence after coronary artery bypass grafting [28], and contrast induced nephropathy in acute ST-segment elevation myocardial infarction (STEMI) patients treated with primary PCI [29]. Moreover, there are some researches about the recent evidence suggested that in patients with STEMI, the admission MHR values were independently correlated with poor prognosis as major adverse cardiovascular events and mortality [3032].…”
Section: Discussionmentioning
confidence: 99%
“…19 Saskin et al claimed that preoperative MHR values were associated with postoperative atrial fibrillation and mortality. 20 In the formation of atherosclerotic plaque, activated circulating monocytes interact with the damaged endothelium and are taken into the intima and turned into macrophages. Macrophages form foam cells by taking LDL and other lipids oxidized with phagocytosis.…”
Section: Discussionmentioning
confidence: 99%